Iron-catalyzed arylmethylation of sulfonyl acrylamides. Issue 36 (7th September 2016) - Yu, Jin-Tao; Hu, Weiming; Peng, Haibo; Cheng, Jiang
Graphical abstract: Highlights: An iron-catalyzed arylmethylation of activated alkenes was developed. Di- tert -butyl peroxide (DTBP) served as the methyl radical source. The cascade methyl radical addition, 1, 4-aryl migration, and desulfonylation was involved. Abstract: A novel iron-catalyzed arylmethylation of activated alkenes was developed using di- tert -butyl peroxide (DTBP) as the methyl radical source. This cascade process involved the sequential methyl radical addition, 1, 4-aryl migration, and desulfonylation of sulfonyl acrylamides to afford a variety of α-aryl-β-methyl amides in good to moderate yields.